2021
DOI: 10.3389/fcell.2021.757260
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Circular RNA CircRFX3 Serves as a Sponge for MicroRNA-587 in Promoting Glioblastoma Progression via Regulating PDIA3

Abstract: An increasing number of studies have indicated that circular RNAs (circRNAs) participate in the progression of numerous tumors. However, the functions of circRNAs in glioblastoma (GBM) remain largely unknown. In this study, we focused on a novel circRNA (hsa_circRFX3_003) that was spliced from RFX3, which we named circRFX3. We confirmed that the expression of circRFX3 was substantially increased in GBM cell lines and clinical GBM tissues. The results of a series of overexpression and knockdown assays indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Therefore, this study aims to screen out new prognostic markers of cervical cancer and reduce the mortality of cervical cancer patients, thereby providing reference for improving the prognosis and realizing individualized targeted therapy. PDIA3 affects the occurrence and development of a variety of cancer tissues and regulates the proliferation of cancer cells, playing a vital role in the prognosis and treatment of malignant tumors [19]. The research by Zou et al [20] suggested that patients with glioma with high PDIA3 expression had poor survival prognosis, and PDIA3 could be used as an independent prognostic biomarker of diffuse glioma, whose down-regulation might contribute to the survival of patients undergoing chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study aims to screen out new prognostic markers of cervical cancer and reduce the mortality of cervical cancer patients, thereby providing reference for improving the prognosis and realizing individualized targeted therapy. PDIA3 affects the occurrence and development of a variety of cancer tissues and regulates the proliferation of cancer cells, playing a vital role in the prognosis and treatment of malignant tumors [19]. The research by Zou et al [20] suggested that patients with glioma with high PDIA3 expression had poor survival prognosis, and PDIA3 could be used as an independent prognostic biomarker of diffuse glioma, whose down-regulation might contribute to the survival of patients undergoing chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the subcellular fractionation and FISH assays, circ-TRIO was located in the cytoplasm of TNBC cells, indicating that circ-TRIO might have the potential to sponge miRNAs. To date, numerous studies have shown that acting as miRNA sponges is among the most significant approaches by which circRNAs exert their functions [44][45][46]. CiRS-7 was the first circRNA that has been proven to exert its functions by acting as a miRNA sponge, possessing more than 70 conventional binding sites for miR-7 [47].…”
Section: Discussionmentioning
confidence: 99%
“…CircRFX3 is generated from the RFX3 gene [ 93 ]. A high circRFX3 expression level was related to poor prognosis in GBM patients.…”
Section: Functional Mechanisms Of Circrnas In Gbmmentioning
confidence: 99%
“…A high circRFX3 expression level was related to poor prognosis in GBM patients. Overexpression of circRFX3 promoted GBM cell proliferation, invasion and migration [ 93 ]. Dual-luciferase and RNA pull-down assays revealed that circRFX3 could sponge miR-587 and that PDIA3 was a direct target of miR-587 [ 93 ].…”
Section: Functional Mechanisms Of Circrnas In Gbmmentioning
confidence: 99%